Spontaneous pneumothorax and ozone levels: is there a relation? - BOSTANCI, KORKUT; KARAKURT, SAİT; ÇELİKEL, TURGAY HÜSEYİN (NOVAMEDIA, 2011)
Study objectives: Although links between meteorological conditions and spontaneous pneumothorax (SP) have been proposed, the reports are controversial. In this study ozone levels, which are known to have some adverse effects on lung tissues, were investigated as a potential triggering factor of SP. At present there is not sufficient information about the effects of ozone on SP. Methods: Of a total 79 pneumothorax patients recruited for the study, 21 secondary pneumothorax cases were excluded. In the remaining 58 SP patients, meteorological data at the time of SP occurrence were recorded. Results: The number of SP patients was higher in spring than in the other seasons (p < 0.05). There was an association between the SP frequency and the average ozone level at different seasons (F 3,52 = 19.45, p = 0.001). The average ozone level was higher in spring (363 +/- 25 Dobson) than during the other seasons (autumn 296 +/- 18 Dobson; summer 321 +/- 26 Dobson; winter 324 +/- 32 Dobson) (p = 0.001). There was a positive correlation between SP frequency and the average ozone values for each season (r = 0.301, p = 0.024). There was no significant correlation between the severity of SP and ozone level (r = 0.236, p = 0.16). Conclusions: The number of SP patients increases in spring when ozone levels are highest. Ozone is known to affect alveolar cells and cause interstitial edema. Ozone causes damage to the lung interstitium by way of oxidative stress. Rupture of unrecognized underlying blebs/bullae has been proposed as a cause of SP. Increased levels of ozone may be a triggering factor for these ruptures.
Keywords: Ozone; seasonality; spontaneous pneumothorax; ATMOSPHERIC-PRESSURE; OUTDOOR TEMPERATURE; EXPOSURE; RISK